Data Retrieval on Heat Exchange Machines - Geralfine, Hilza Arrun; Mahmudah, Imam; Perdana, Rizky Ridho; Naufal, Ananda; Hermaputra, Virendra Maulana; Bagindo, Fikran Azizi; Witjaksono, Yoga Aiman; Saputro , W (BIOMEJ, 2024)
In many industrial processes, heat transfer—the movement of thermal energy from one object or medium to another—is a significant phenomena. Conduction, convection, and radiation are the three primary mechanisms via which this phenomena happens. When a temperature gradient causes heat to go from a hotter to a cooler region in a solid substance, this process is known as conduction. Heat is transferred through a moving fluid (liquid or gas) by convection, which can occur spontaneously as a result of density differences or be induced mechanically by a pump or fan. Unlike the other two methods, radiation includes the movement of energy in the form of electromagnetic waves and does not require a medium.